The seroprevalence of anti-Histoplasma capsulatum IgG antibody among pulmonary tuberculosis patients in seven referral tuberculosis hospitals in Indonesia. - Tutik Kusmiati; Erlina Burhan; Retna Indah Sugiyono; Dona Arlinda; Adhella Menur Naysilla; Banteng Hanang Wibisono; Riat El Khair; Ni Wayan Candrawati; Bintang Yinke Magdalena Sinaga; Irawaty Djaharrudin; Dewi Lokida; Herman Kosasih; et al. (PLoS Neglected Tropical Diseases)
Background Histoplasma capsulatum exposure is rarely suspected in Indonesia. Pulmonary histoplasmosis can occur simultaneously with pulmonary tuberculosis (TB) or as an alternative diagnosis in clinically-diagnosed TB patients with no microbiological evidence of TB. This study aimed to determine the seroprevalence of anti-H. capsulatum IgG antibody among pulmonary TB patients. Methodology This was a sub-study of 306 participants from a prospective cohort pulmonary TB study conducted at seven TB referral hospitals in Indonesia. The study population was presumptive pulmonary TB adult patients who underwent microbiological TB examinations and were categorized as drug-sensitive (DS), drug-resistant (DR), and clinically-diagnosed TB. Anti-H. capsulatum IgG antibody levels at baseline were measured using MVista Histoplasma Ab enzyme immunoassays. Data were summarized using descriptive statistics. Bivariate and multivariate logistic regression analysis were performed to assess factors associated with anti-H. capsulatum IgG antibody positive result. Results 12.7% (39/306) of pulmonary TB patients were positive for anti-H. capsulatum IgG antibodies (DR-TB patients (15.9%, 18/114), DS-TB (13.0%, 15/115), and clinically-diagnosed TB (7.8%, 6/77)). The median unit value of anti-H. capsulatum IgG antibody for all positive samples was 15.7 (IQR 10.2-28.9) EU. This median unit value was higher in clinically-diagnosed TB patients compared to DS-TB or DR-TB patients (38.1 (IQR 25.6-46.6) EU, 19.7 (IQR 12.3-28.9) EU, and 10.9 (IQR 9.2-15.4), respectively). There were 10 patients (3.3%) with anti-H. capsulatum IgG antibody levels above 30 EU. Factors associated with the anti-H. capsulatum IgG antibody positive result were malignancies (OR 4.88, 95% CI 1.09-21.69, p = 0.037) and cavitary lesions (OR 2.27, 95% CI 1.09-4.70, p = 0.028). Conclusions Our results provide evidence of exposure to H. capsulatum among pulmonary TB patients in Indonesia. Further studies are needed to provide a comprehensive picture of this fungal disease in other populations and regions to enhance awareness among clinicians and public health officials.